Novel hybrid image compression–encryption algorithm based on compressive sensing - Zhou, Nanrun; Zhang, Aidi; Wu, Jianhua; Pei, Dongju; Yang, Yixian (Optik (Stuttgart), 2014)
A new hybrid image compression–encryption algorithm based on compressive sensing is proposed, which can accomplish image encryption and compression simultaneously. The partial Hadamard matrix is adopted as measurement matrix, which is controlled by chaos map. The measurement is scrambled. Compared with the methods adopting the Gaussian random matrix as measurement matrix, and those using the whole measurement matrix as key, the proposed algorithm reduces the burden of transferring key and is more practical. The proposed algorithm with sensitive keys and nice image compression ability can resist various attacks. Simulation results verify the validity and reliability of the proposed algorithm.